Failure analysis of micro-channel condenser of air source heat pump water heater. (April 2021) - Zhang, Piji; Dong, Weili; Wang, Lida; Sun, Wen; Liu, Bingyan; Yang, Zhengqing; Liu, Guichang
Highlights: The failure of microchannel condenser of air source heat pump water heater is studied. HCl-HF acidic aqueous medium inside the condenser caused corrosion of aluminium alloy. Corrosive medium is constructed by water and decomposition product of refrigerant. Water provides continuous electrolyte for corrosion, so must be avoided in condenser. Abstract: Air source heat pump water heaters (ASHPWH) fail during service, due to the leakage of the micro-channel condensers. Failure analysis of the condenser was carried out through a series of characterization methods, including energy dispersive X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Results reveal that the failure of these condensers results from the corrosion of aluminium alloy in acidic aqueous medium, which is constructed by external introduced water and the decomposition products of refrigerant during service. Additionally, the deterioration of refrigeration oil, the abnormal operation of compressor, and the internal defects of condensers also contribute to the failure of the condensers. Finally, a series of countermeasures are proposed for avoiding the corrosion failure of such condensers.